HYGIENIC ASPECTS OF STORAGE AND PROCESSING OF FOOD RAW MATERIALS UNDER CERTAIN CONDITIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, the quality and safety of products, which are very important in the food sector, the issue of prevention of infectious diseases, legal and economic aspects, training and education, technological reforms, types of technological processing of raw materials and products used in food preparation the importance of food products and raw materials and technological processing is discussed.